Real interpolation of Sobolev spaces
We prove that W^1_p is a real interpolation space between W^1_p_1 and W^1_p_2 for p>q_0 and 1≤ p_1<p<p_2≤ ∞ on some classes of manifolds and general metric spaces, where q_0 depends on our hypotheses., number=2, journal=MATHEMATICA SCANDINAVICA, author=Badr, Nadine, year=2009, month=Dec., pages=235–264